EASI: Volume 4, Issue 2. [Special issue] - Samaniego-Riera, Franklin (EASI: Engineering and Applied Sciences in Industry, 2025)
The study and application of AI, together with simulation and prospective models, enable us to tackle new industrial and environmental challenges. Functional prototypes therefore improve efficiency, sustainability, and decision-making in various sectors through innovative, data-driven technological solutions. Explore articles that inspire simulation and in-depth analysis of new technologies. Immerse yourself in this new work presented by EASI.